Effect of Sexual Skills Counseling With Cognitive-Behavioral Approach on Sexual Assertiveness in Women Suffering from Marital Disillusionment - Faezeh Saffari Mofrad; sakineh Taherkhani; Ashraf Khoramirad (مراقبت پرستاری و مامایی ابن سینا)
Background and Objective: Marital disillusionment is associated with adverse consequences for individuals, couples, families, and society. Low sexual assertiveness paves the way for marital disillusionment. The present study aimed to determine the effect of sexual skills counseling with a cognitive-behavioral approach on sexual assertiveness in women suffering from marital disillusionment. Materials and Methods: This study was a clinical trial involving 80 women experiencing marital disillusionment selected from comprehensive health centers affiliated with Qom University of Medical Sciences, Qom, Iran. They were assigned to intervention and control groups. Eight weekly sessions were held for the intervention group. Data were collected using demographic questions, the marital disillusionment scale (MDS) and Halbert index of sexual assertiveness. Sexual assertiveness was remeasured immediately and 12 weeks after the end of the intervention.  Data was analyzed using the SPSS (version 23) software using independent t-test, Chi-square test, Fisher’s exact test, and repeated measures ANOVA. Results: The mean score of sexual assertiveness did not have a statistically significant difference between the groups before the intervention. The mean and standard deviation of the sexual assertiveness score in the intervention group changed from 34.1±11.67 before the intervention to 74.9±11.68 and 56.8±8.46 in the post-test and follow-up periods, respectively. These values for the control group were 33.5±11.00, 36.7±10.64, and 37.3±11.08, respectively. According to the results, the mean score of sexual assertiveness between the intervention and control groups and at the examined three time points had a statistically significant difference (P<0.001). Conclusion: Sexual skills counseling with a cognitive-behavioral approach led to an increase in sexual assertiveness in women suffering from marital disillusionment. Therefore, this approach can be used as an effective psychological intervention to increase sexual assertiveness in these women.